2014
DOI: 10.1007/jhep12(2014)017
|View full text |Cite
|
Sign up to set email alerts
|

Identification techniques for highly boosted W bosons that decay into hadrons

Abstract: Abstract:In searches for new physics in the energy regime of the LHC, it is becoming increasingly important to distinguish single-jet objects that originate from the merging of the decay products of W bosons produced with high transverse momenta from jets initiated by single partons. Algorithms are defined to identify such W jets for different signals of interest, using techniques that are also applicable to other decays of bosons to hadrons that result in a single jet, such as those from highly boosted Z and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(121 citation statements)
references
References 52 publications
2
119
0
Order By: Relevance
“…We remark that enhancing sensitivity to either the center or edges of the cos θ q distribution will emphasize sensitivity to longitudinal or transverse gauge bosons, respectively. These results also agree with an earlier analysis by CMS [125], but we carry the analysis further by studying multiple stateof-the-art jet substructure techniques to understand the impact of vector boson polarization on the resulting reconstruction efficiency.…”
Section: Jhep09(2016)036supporting
confidence: 87%
“…We remark that enhancing sensitivity to either the center or edges of the cos θ q distribution will emphasize sensitivity to longitudinal or transverse gauge bosons, respectively. These results also agree with an earlier analysis by CMS [125], but we carry the analysis further by studying multiple stateof-the-art jet substructure techniques to understand the impact of vector boson polarization on the resulting reconstruction efficiency.…”
Section: Jhep09(2016)036supporting
confidence: 87%
“…Previous studies [43,44] have shown disagreement in the pruned jet mass spectra between data and simulation when a τ 21 requirement is applied. The method used to quantify this discrepancy is described in Ref.…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%
“…The method used to quantify this discrepancy is described in Ref. [44], and is based on measuring the efficiency of identifying boosted two-prong W bosons in semileptonic tt events. For τ 21 < 0.45, the ratio of the efficiencies in data and simulation, or scale factor, is measured to be 1.10 ± 0.13.…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%
“…This equips us to extract most of the required information by considering a small fraction of the trees, in a computationally efficient manner. As already mentioned, many aspects of this paradigm has already been validated at the LHC, by both the ATLAS and CMS collaborations [59][60][61][62].…”
Section: The Qjets Paradigmmentioning
confidence: 99%